Do Nonseminomatous Germ Cell Tumors of the Testis With Lymphovascular Invasion of the Spermatic Cord Merit Staging as pT3?. (October 2017) - Gordetsky, Jennifer; Sanfrancesco, Joseph; Epstein, Jonathan I.; Trevino, Karen; Xu, Huiping; Osunkoya, Adeboye; Xiao, Guang Q.; Kao, Chia-Sui; Unger, Pamela; Hashemi-Sadraei, Neda; Albany, Constantine; Jorns, Julie M.; et al.
Abstract : The staging of testicular nonseminomatous germ cell tumors (NSGCTs) with lymphovascular invasion (LVI) of the spermatic cord in the absence of cord parenchymal involvement remains controversial. Our previous study showed that tumors with spermatic cord LVI present at a higher clinical stage than tumors with LVI confined to the testis (pT2). We compared NSGCTs with LVI of the spermatic cord without direct involvement of the spermatic cord soft tissues to pT3 tumors to help clarify the appropriate staging of this histologic finding. A retrospective, multi-institutional review was performed to identify cases of NSGCTs with LVI in the spermatic cord without soft tissue invasion of the cord. The clinical-pathologic findings were compared with NSGCTs with spermatic cord soft tissue invasion (pT3). We identified 38 pT2 NSGCTs with LVI in the spermatic cord without soft tissue invasion of the cord and 89 pT3 tumors. There were no significant differences in patient age, tumor size, or clinical stage at presentation between the 2 groups. There were no significant differences in dominant histologic subtype, rete testis invasion, hilar soft tissue invasion, or margin status. There were no significant differences in disease recurrence/progression ( P =0.63), recurrence/progression after chemotherapy ( P =0.35), or death ( P =0.51) between patients with only spermatic cord LVI versus patients with cord soft tissue invasion. In patients with pT2 NSGCTs according to the current staging, LVI in the spermatic cord without cord soft tissue invasion is comparable with pT3 tumors in terms of clinical stage at presentation as well as disease recurrence and survival.